Alpha-synuclein aggregates in the parotid gland of idiopathic REM sleep behavior disorder - Fernández-Arcos, Ana; Vilaseca, Isabel; Aldecoa, Iban; Serradell, Mónica; Tolosa, Eduard; Santamaría, Joan; Gelpi, Ellen; Iranzo, Alex (Sleep medicine, 2018)
The neuropathological hallmark of Parkinson's disease (PD) is the presence of aggregates of phosphorylated alpha-synuclein (pAS) in the nervous system. We report a patient with video-polysomnography-confirmed idiopathic REM sleep behavior disorder that underwent parotidectomy because of parotid gland cancer. Immunohistochemistry of the gland tissue revealed abundant pAS deposits. One year after surgery the patient was diagnosed with PD. Prompted by this observation we examined the parotid gland in 10 consecutive individuals that underwent elective parotidectomy irrespective of their clinical condition. One had PD and another had mild parkinsonian signs plus reduced dopamine transporter uptake in the striatum. Both had pAS deposits in the parotid gland. The remaining eight subjects had no neurological signs and pAS was found in one of them. Our study shows that the parotid gland may contain pAS pathology in the prodromal stage of PD and in manifested PD. •Intraneuronal aggregates of phosphorylated alpha-synuclein are the pathological hallmark of Parkinson's disease.•In idiopathic REM sleep behavior disorder the parotid gland may contain inclusions of alpha-synuclein, suggesting that this parasomnia represents prodromal Parkinson's disease.•In manifested Parkinson's disease the parotid gland may contain inclusions of alpha-synuclein.